Seroprevalence of hepatitis B and vaccine effectiveness in vertical transmission prevention: a hybrid study among pregnant mothers attending antenatal clinics in Abyei, South Sudan - Matueny, Ramzy M.; Owino, Alfred O.; Muchiri, Joseph; Nyamai, Joseph J. (International Journal Of Community Medicine And Public Health, 2024)
Background: Hepatitis B virus (HBV) is a global health threat, affecting millions worldwide and causing severe liver diseases such as cirrhosis and cancer. Low and middle-income countries (LMICs), particularly South Sudan, face challenges like limited healthcare infrastructure and public awareness, leading to high HBV prevalence. Infants born of seropositive women are at heightened risk due to vertical transmission, perpetuating the infection cycle. Methods: This study assessed HBV seroprevalence among pregnant women in Abyei, South Sudan, and evaluated vaccine effectiveness in preventing mother-to-child transmission. A hybrid study of cross-sectional and cohort design included 384 pregnant women and 94 infants. Blood samples were tested for hepatitis B surface antigen (HBsAg), while socio-demographic data and awareness levels were gathered through structured questionnaires. Qualitative insights were also collected via focus group discussions and interviews with healthcare providers. Logistic regression was used to analyze risk factors. Results: The seroprevalence of HBV was 19% among pregnant women. Younger age, lower education levels, and unemployment were associated with higher infection rates. Vertical transmission occurred in 4.3% of infants, despite vaccine availability. Awareness of HBV was notably low among participants, underscoring gaps in public health education. Conclusions: HBV presents a significant health burden in Abyei, South Sudan. Enhancing health education, improving access to preventive strategies, and strengthening healthcare infrastructure are critical to reducing HBV prevalence and transmission. Implementing targeted public health interventions can mitigate the virus’s impact on maternal and child health in the region.